2014
DOI: 10.2134/jeq2013.10.0405
|View full text |Cite
|
Sign up to set email alerts
|

Net Global Warming Potential and Greenhouse Gas Intensity Influenced by Irrigation, Tillage, Crop Rotation, and Nitrogen Fertilization

Abstract: Little information exists about how global warming potential (GWP) is affected by management practices in agroecosystems. We evaluated the effects of irrigation, tillage, crop rotation, and N fertilization on net GWP and greenhouse gas intensity (GHGI or GWP per unit crop yield) calculated by soil respiration (GWP and GHGI) and organic C (SOC) (GWP and GHGI) methods after accounting for CO emissions from all sources (irrigation, farm operations, N fertilization, and greenhouse gas [GHG] fluxes) and sinks (crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
74
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 36 publications
8
74
0
2
Order By: Relevance
“…However, the release of CO 2 during the manufacturing and application of N fertilizer to crops and from fuel used in machines for farm operations can counteract these mitigation efforts (West and Marland, 2002). Therefore, when determining the GWP of agroecosystems, there is a need to account for all sources of GHG emissions, including the emissions associated with agrochemical input (Ei) and farm operation (Eo) and sinks, e.g., soil organic carbon (SOC) sequestration (Sainju et al, 2014).…”
Section: Zhang Et Al: Global Warming Potential and Greenhouse Gasmentioning
confidence: 99%
“…However, the release of CO 2 during the manufacturing and application of N fertilizer to crops and from fuel used in machines for farm operations can counteract these mitigation efforts (West and Marland, 2002). Therefore, when determining the GWP of agroecosystems, there is a need to account for all sources of GHG emissions, including the emissions associated with agrochemical input (Ei) and farm operation (Eo) and sinks, e.g., soil organic carbon (SOC) sequestration (Sainju et al, 2014).…”
Section: Zhang Et Al: Global Warming Potential and Greenhouse Gasmentioning
confidence: 99%
“…They observed this because (1) no nitrogen fertilizer was applied to legumes compared with nonlegumes which required large amount of nitrogen fertilizers to sustain yields, as nitrogen fertilizer stimulates N 2 O emissions and (2) legumes supplied greater amount of nitrogen to succeeding crops due to higher nitrogen concentration when above-and belowground residues were returned to the soil and reduced nitrogen fertilization rate compared with nonlegumes. Sainju et al [9,10] also found that legume-nonlegume rotation increased soil carbon sequestration because of increased turnover rate of plant carbon to soil carbon compared to continuous nonlegume.In a meta-analysis of 11 experiments on the effect of crop rotation containing small and large grain crops on net GWP and GHGI, Sainju [56] reported that crop rotation increased net GWP by 46% and net GHGI by 41% compared with monocropping. This was especially true for large grain crops, such as corn and soybean where net GWP and GHGI were 215 and 325%, respectively, greater under corn-soybean than continuous corn.…”
mentioning
confidence: 97%
“…In contrast, greater N 2 O emissions following soybean increased net GWP and GHGI in corn-soybean rotation [3,7,48,49]. Under small grain crops, however, several researchers [9,10,60,61] have found that including legumes, such as pea and lentil, in rotation with nonlegumes, such as wheat and barley, reduced net GWP and GHGI compared with continuous nonlegumes. They observed this because (1) no nitrogen fertilizer was applied to legumes compared with nonlegumes which required large amount of nitrogen fertilizers to sustain yields, as nitrogen fertilizer stimulates N 2 O emissions and (2) legumes supplied greater amount of nitrogen to succeeding crops due to higher nitrogen concentration when above-and belowground residues were returned to the soil and reduced nitrogen fertilization rate compared with nonlegumes.…”
mentioning
confidence: 99%
See 2 more Smart Citations